Contribution to the knowledge of the structure of beetle cenoses from the “Cosauti” (insecta: coleoptera) landscape reserve [Articol] - Enciu, Elena (My University, 2023)
This work presents data on the fauna and beetle’s species diversity in some forest ecosystems in northern Moldova. As a result of collections during the year 2017, there were identified in the investigated forest ecosystems 48 species belonging to 31 genera and 7 families (Carabidae, Cantharidae, Silphidae, Geotrupidae, Scarabaeidae, Lucanidae and Cerambycidae), of which 4 ones are rare and extinction endangered species, included in the third edition of the Red Book of Moldova. After trophic preferences, most identified species of beetles belong to the phytophagous group – 43%, followed by the zoofagous group – 41%. Coprophagous represent 5%, xylophagous – 5%, mixophytophagous – 4%, and necrophagous – 2%. According to the distribution area, the European (17) and Trans-Palearctic (15) species dominate.

Această lucrare prezintă date despre fauna și diversitatea coleopterelor din 2 ecosisteme forestiere din rezervația peisagistică ”Cosăuți”. În rezultatul cercetărilor efectuate în anul 2017, în ecosistemele forestiere investigate au fost identificate 48 de specii aparținând a 31 de genuri și 7 familii (Carabidae, Cantharidae, Silphidae, Geotrupidae, Scarabaeidae, Lucanidae și Cerambycidae), dintre care 4 sunt rare și pe cale de dispariție, incluse în a treia ediție a Cărții Roșii a Moldovei. După preferințele trofice, majoritatea speciilor de coleoptere identificate aparțin grupului fitofagilor – 43%, urmat de grupul zoofagilor – 41%. Coprofagii reprezintă 5%, xilofagii – 5%, mixofitofagii – 4% și necrofagii – 2%. După aria de răspândire, predomină speciile europene (17) și transpalearctice (15).
Keywords: coleoptere; diversitate; spectru trofic; indici ecologici; beetles; biodiversity; trophic spectrum; ecological indexes